“White spots” of the generational analysis: Objective and subjective meaning of the age - I V Trotsuk (RUDN journal of Sociology, 2015)
As a rule, it goes without saying that the generational analysis is one of the major tasks of sociology, which aims to diagnose the state and trends of the social development by comparing value priorities, attitudes and behavioral patterns of the age subgroups that constitute the society. Despite the lack of a common definition of ‘generation’ in the scientific discourse and the differences in its interdisciplinary interpretations researchers agree that in sociology we define ‘generation’ not so much as a demographic group of the same age, but as a certain symbolic community whose members were raised in the similar social conditions. Unfortunately, the Russian sociology adheres to the fragmented version of generational analysis focusing mainly on the youth (less often on the working population as a whole) and ‘forgets’ about the elderly and children due to several reasons, but the main ones are evident in both cases - the older generations are largely ignored, and for the youngest it is difficult to choose an adequate methodological approach. The article indicates the thematic priorities of generational analysis in its sociological format (focus on the social status and symbolic features of generations rather than on the culture of childhood, which is the subject of historical research), identifies its key concepts (generation and cohort) and problems, summarized the differences of the methodological approaches (primarily quantitative and qualitative) and research orientations especially in the study of older ages.